PENGARUH SELEBRITI ENDORSE DAN ISLAMI BRANDING TERHADAP LOYALITAS KONSUMEN DI 212 MART KOTA BENGKULU - Helfiliani, Juita; Sismanto, Adi (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
The increasing competition in the business world compels producers to develop more effective marketing strategies to attract and maintain consumer loyalty to their products. Producers are not only required to produce high-quality products but are also expected to meet consumer needs and preferences by offering various relevant product choices. This study aims to determine the influence of celebrity endorsers and Islamic branding on consumer loyalty at 212 Mart in Bengkulu City.This research adopts a descriptive quantitative approach and is conducted at 212 Mart in Bengkulu City. The sampling method used was accidental sampling, with a total of 100 respondents. The data collection was carried out through questionnaires. The data analysis techniques included the multiple linear regression analysis, determination coefficient analysis, and hypothesis testing. Based on the processed data, the regression equation obtained through SPSS computation is Y = 3.064+0.302 X1 +0.440 X2 + e, with an R Square (R²) value of 0.669, indicating that the independent variables contribute 66.9% to the dependent variable. The hypothesis test results show that celebrity endorsers and Islamic branding together have a positive and significant influence on consumer loyalty at 212 Mart in Bengkulu City. Keywords: Celebrity Endorser, Islamic Branding, and Consumer Loyalty